2004
DOI: 10.1007/bf02287291
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of care: Validation of a new self-report measure for individuals using mental health services

Abstract: Continuity of care is a concern for individuals with persistent mental illness who need diverse services over time in response to multiple and changing needs. Efforts to study continuity have been hampered by lack of appropriate instruments. The Alberta Continuity of Services Scale--Mental Health is a newly developed, self-report scale that assesses continuity of care across settings and providers. This study examined the structure, reliability, and validity of the measure among users of community mental healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(90 citation statements)
references
References 37 publications
4
83
1
2
Order By: Relevance
“…These factors demonstrate reasonable correspondence with the domains identified in our development work (Joyce et al 2004). Durbin et al (2004) also reported associations between their factors and selected respondent and service use measures which offered evidence for the validity of the measure.…”
Section: Goals Of the Present Studymentioning
confidence: 98%
See 1 more Smart Citation
“…These factors demonstrate reasonable correspondence with the domains identified in our development work (Joyce et al 2004). Durbin et al (2004) also reported associations between their factors and selected respondent and service use measures which offered evidence for the validity of the measure.…”
Section: Goals Of the Present Studymentioning
confidence: 98%
“…A previous validation study of the ACSS-MH, based on data from community and outpatient mental health programs in the province of Ontario, has been published (Durbin et al 2004). The factor structure, reliability, and validity of the instrument was examined in a sample of 215 respondents.…”
Section: Goals Of the Present Studymentioning
confidence: 99%
“…Other standardized instruments used in data collection were: (1) the Multnomah Community Ability Scale (MCAS), which assesses functional status in the community (e.g., obstacles to functioning, social competencies; CA: 0.87) (Barker et al 1994); (2) the Social Provisions Scale (SPS), which determines level of integration and social support (e.g., reassurance about one's value, the need to feel useful; CA: 0.92) (Cutrona 1989); (3) the Satisfaction with Life Domains Scale (SLDS), which assesses quality of life (e.g., daily living, social relationships; CA: 0.92) (Baker et al 1992); (4) the Alcohol Use Disorders Identification Test (AUDIT), which measures alcohol consumption and consequences (CA: 0.88) (Bohn et al 1995); (5) the Drug Abuse Screening Test-20 (DAST-20) which evaluates participant drug use and consequences (CA: 0.74) (Skinner 1982); (6) the Alberta Continuity of Services Scale for Mental Health (ACSS), a measuring of service continuity (e.g., system access, team function; CA: 0.78 to 0.92) (Durbin et al 2004); and (7) the Service Utilization Questionnaire (SUQ), derived from the Canadian Community Health Survey Questionnaire (Gravel and Béland 2005), which evaluates types of professionals consulted (e.g., general practitioner, psychiatrist) for mental health reasons in the 12-month period prior to recruitment. Total scores were compiled on all seven instruments, although a number of sub-scales for some instruments may have yielded findings of interest.…”
Section: Instrumentsmentioning
confidence: 99%
“…Understanding help-seeking, or the steps through which families move on their way to receiving treatment, may help to close the gap between those children needing and receiving mental health services (Durbin et al 2004;Zwaanswijk et al 2003).…”
mentioning
confidence: 99%